Самооценка деятельности предприятия по методу "бережливое производство" - Лысенко, Ю. Н.; Гриднева, Г. И.; Косарева, И. Н.; Кобзева, А. Г. (НТУ "ХПИ", 2014)
В данной статье рассмотрен инструмент самооценки предприятия, позволяющий определить его потребность в применении методов бережливого производства. По данным таблицы, составленной по определенным аспектам стратегии производства, строится схема-радар, наглядно представляющая результат самооценки. С помощью данного инструмента можно исследовать, измерять и оценивать состояние дел в ключевых областях производства, выявлять основные проблемные зоны и вырабатывать по ним оптимальные решения.

This article describes a self-evaluation tool the company, allowing it to determine its need for the application of lean production methods. With this tool you can explore, measure, and assess the state of Affairs in key areas of production, to identify the main problem areas and reach the optimal solution. According to the tables on specific aspects of the production strategy, the circuit is constructed radar, vividly representing the result of self-assessment. With schema-radar is the self-esteem of the enterprise and develop measures to eliminate bottlenecks in production. For example, improving product quality, search for new suppliers, improvement of production technology, equipment modernization, expansion of production.
The self-assessment activities by the method of "lean production"
Keywords: конкурентоспособность; инструмент самооценки предприятия; методы бережливого производства; схема-радар; ean production; self-esteem enterprise; scheme-radar